Comparative Study Between Fosaprepitant and Palonosetron in the Prophylaxis of Postoperative Nausea and Vomiting in Women Undergoing Laparoscopic Cholecystectomy: Prospective, Randomized and Double-Blind Study - Braga, Estêvão Luiz Carvalho; Verçosa, Nubia; Cavalcanti, Ismar Lima (Frontiers in Pharmacology, 2022)
Objective: To test the hypothesis that the single use of fosaprepitant is not inferior to the use of palonosetron as antiemetic prophylaxis in the first 48 h after surgery in women undergoing laparoscopic cholecystectomy. Method: Eighty-eight nonsmoking women (American Society of Anesthesiologists physical status I or II) aged between 18 and 60 years who underwent laparoscopic cholecystectomy received 150 mg of fosaprepitant or 75 μg of palonosetron, administered intravenously after the induction of general anesthesia. Results: In the fosaprepitant group and in the palonosetron group, 13.6 and 18.2% of the patients, respectively, vomited in the first 48 h after surgery (p = 0.560). There were no differences between groups in the total frequency and intensity of nausea, number of complete responders, need for rescue medication, time required for the first rescue medication dose or number of adverse events. Conclusion: The administration of a single dose of fosaprepitant after the induction of anesthesia was as effective as the administration of a single dose of palonosetron for the prophylaxis of vomiting in the first 48 h after surgery in women undergoing laparoscopic cholecystectomy.